Indiscriminate chemical use in Kerala: Special emphasis to reproductive changes by endocrine disrupting chemicals - and Soumya Sankar., Rejitha Joseph . (International Journal of Scientific Research and Management (IJSRM), 2017)
Some of the insecticides and pesticides are known as endocrine disrupting (ED) chemicals that have the property to alter normal functioning of endocrine system. In this paper the hazardous properties of some pesticides liberally used in Kerala and their physiological effects with special emphasis to disorders in reproductive system are reviewed. The aim of the present review is to give an overview of various ways in which EDs may disrupt the reproductive hormonal function. Endocrine disturbing chemicals disturb the mechanism of hormone synthesis, storage, release and action through getting into various steps and modulating various enzymes involved. Altered hormonal profile result in sub fertility or infertility of individuals and effect of chemicals on gametes are resulting in genetic defect. General awareness on adverse effect of pesticide, controlled use of pesticide and biological pest control has to be disseminated among the farmers of Kerala. It is necessary to establish a double pricing system to agricultural products of organic farming in Kerala for promoting organic farming among the farmers.